Recapitulation of in vivo-like paracrine signals of human mesenchymal stem cells for functional neuronal differentiation of human neural stem cells in a 3D microfluidic system. (September 2015) - Yang, Kisuk; Park, Hyun-Ji; Han, Sewoon; Lee, Joan; Ko, Eunkyung; Kim, Jin; Lee, Jong Seung; Yu, Ji Hea; Song, Ki Yeong; Cheong, Eunji; Cho, Sung-Rae; Chung, Seok; et al.
Abstract: Paracrine signals produced from stem cells influence tissue regeneration by inducing the differentiation of endogenous stem or progenitor cells. However, many recent studies that have investigated paracrine signaling of stem cells have relied on either two-dimensional transwell systems or conditioned medium culture, neither of which provide optimal culture microenvironments for elucidating the effects of paracrine signals in vivo . In this study, we recapitulated in vivo -like paracrine signaling of human mesenchymal stem cells (hMSCs) to enhance functional neuronal differentiation of human neural stem cells (hNSCs) in three-dimensional (3D) extracellular matrices (ECMs) within a microfluidic array platform. In order to amplify paracrine signaling, hMSCs were genetically engineered using cationic polymer nanoparticles to overexpress glial cell-derived neurotrophic factor (GDNF). hNSCs were cultured in 3D ECM hydrogel used to fill central channels of the microfluidic device, while GDNF-overexpressing hMSCs (GDNF-hMSCs) were cultured in channels located on both sides of the central channel. This setup allowed for mimicking of paracrine signaling between genetically engineered hMSCs and endogenous hNSCs in the brain. Co-culture of hNSCs with GDNF-hMSCs in the 3D microfluidic system yielded reduced glial differentiation of hNSCs while significantly enhancing differentiation into neuronal cells including dopaminergic neurons. Neuronal cells produced from hNSCs differentiating in the presence of GDNF-hMSCs exhibited functional neuron-like electrophysiological features. The enhanced paracrine ability of GDNF-hMSCs was finally confirmed using an animal model of hypoxic-ischemic brain injury. This study demonstrates the presented 3D microfluidic array device can provide an efficient co-culture platform and provide an environment for paracrine signals from transplanted stem cells to control endogenous neuronal behaviors in vivo .